KONFLIK ANTAR NILAI BAGI SUKSESI PERUBAHAN KEBIJAKAN DALAM PENGEMBANGAN ORGANISASI - Apriani, Fajar (JAKPP (Jurnal Analisis Kebijakan & Pelayanan Publik), 2019)
Besides the allocation of various resources, the allocation of values to manage various interests through public policy is the background of the emergence of conflict. The high potential of conflict requires the presence of a policy maker who can be in a neutral position. But in the reality of organizational life, the resulting public policy often triggers conflict itself. The cause of conflict is the variation and conflict of values or interests held by each actor. In general, such conditions are further exacerbated by the way public policy is managed which tends to ignore values and value conflicts as well as elitist-technocratic managed policy processes that limit or minimize the space of reasoning between interest actors. This condition becomes an obstacle in policy succession as part of policy changes for organizational development. Then a leader of an organization must be able to identify the orientation dimensions of conflict handling and be aware of the right conditions or situations to do so because understanding and decision making regarding appropriate conflict handling steps will be able to bring the organization to the use of functional conflicts for organizational development.